Peran Standar Pengelolaan PAUD dalam Meningkatkan Perkembangan Sosial Anak Usia Dini - Hilma Tsamrotun Najah; Astuti Darmiyanti (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2024)
This research discusses the role of preschool management standards in improving early childhood social development in Indonesia. preschool plays a crucial role in children's development, with curriculum, teaching methods, infrastructure, and parental and community involvement being key elements in ensuring quality education. Good preschool management standards can create a conducive learning environment, encourage healthy social interactions, and support the development of children's social skills. The research uses the literature study method by collecting data from various relevant sources such as books, scientific journals, articles and official documents. The analysis shows that Total Quality Management (TQM) indicators, such as leadership, commitment, customer focus, data measurement and analysis, and continuous improvement, can be applied in preschool management to improve service quality. Although there are implementation constraints, such as uneven quality of preschool and lack of a comprehensive assessment system, this study provides recommendations to improve access to educational resources, develop an objective assessment system, and increase parental and community involvement. With collaborative efforts from various parties, the quality of early childhood education in Indonesia can be improved, ultimately supporting children's optimal social development.